Implementation Of Direct Reading Thinking Activity In Learning To Read In Arabic Lessons - Mohamad Yahya Ashari; Mokhammad Miftakhul Huda; Rifatul Mahfudhoh (Journal of Arabic Language Teaching, 2023)
This study focused on the study of the implementation of the strategy DRTA (Directed Reading Thinking Activity) in learning to read in MTsN 15 Jombang. Obstacles faced in implementing the DRTA strategy and solutions made by Arabic teachers in the face of blocks in the teaching and learning process in Class 8-F. The research method used in this study is qualitative research. This research was conducted in MTsN 15 Jombang by involving the components in the madrasah as a data source or the research subject. The methods that researchers use in this study to collect data are observation methods, interview methods, and documentation methods. Based on the data findings in the field, the researcher can conclude that the process of implementation of the strategy DRTA in learning to read can be classified as part of the read-aloud, reading in the liver, and reading the analytical. Therefore, the strategy requires students to gain the ability to understand the text of a precise reading through systematic learning steps, ranging from reading aloud or inwardly to drawing conclusions based on the assignment given by connecting various knowledge that students have before and after reading. Implementation of the DRTA strategy, there are several obstacles faced. Still, Arabic teachers also make some efforts to overcome these obstacles so that Arabic language learning in Grades 8-F can run optimally, one of which is by forming study groups and student assignments and providing motivation to students by always giving confidence about the benefits of Arabic for the future of students both in religious life in the face of the global era.